2006
DOI: 10.1111/j.1744-6570.2006.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Keen to Help? Managers' Implicit Person Theories and Their Subsequent Employee Coaching

Abstract: Although coaching can facilitate employee development and performance, the stark reality is that managers often differ substantially in their inclination to coach their subordinates. To address this issue, we draw from and build upon a body of social psychology research that finds that implicit person theories (IPTs) about the malleability of personal attributes (e.g., personality and ability) affect one's willingness to help others. Specifically, individuals holding an "entity theory" that human attributes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
393
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(409 citation statements)
references
References 80 publications
12
393
0
4
Order By: Relevance
“…In contrast, when teachers believed that intelligence was malleable they provided increased support and reported instructional goals that explicitly taught students how to problem solve (Swann & Snyder, 1980). Similar research outside of the educational field confirms that individual mindset may impact work with subordinates or mentees (Heslin, Vandewalle & Latham, 2006). In the workplace, managers with a growth mindset were more likely to coach and help employees than were managers who believed that their subordinates' traits and abili-ties were fixed.…”
Section: Introductionmentioning
confidence: 63%
“…In contrast, when teachers believed that intelligence was malleable they provided increased support and reported instructional goals that explicitly taught students how to problem solve (Swann & Snyder, 1980). Similar research outside of the educational field confirms that individual mindset may impact work with subordinates or mentees (Heslin, Vandewalle & Latham, 2006). In the workplace, managers with a growth mindset were more likely to coach and help employees than were managers who believed that their subordinates' traits and abili-ties were fixed.…”
Section: Introductionmentioning
confidence: 63%
“…It has been explained 88.0 percent on the overall variance. In relation, the reliability for the instrument translated version is 0.978 representing all three factors well as the original instrument by Heslin et al (2006). It has provided a strong justification to the use of this instrument in educational organizations in Malaysia.…”
mentioning
confidence: 99%
“…251 lecturers from four polytechnics in Sarawak and Penang have been selected randomly to take part in this study. A total of 13 translation items were adapted from the original instrument of coaching communication developed by Heslin, VandeWalle, and Latham (2006) for the purpose of this study. Three factors have emerged initially through exploratory factor analysis on the collected data.…”
mentioning
confidence: 99%
“…For example, managers might be motivated to foster high quality work design when they have implicit theories about employees as being active organisms who strive for development (Theory Y;McGregor, 1960), are guided by long term organizational development goals (Clegg & Fitter, 1981), or when they clearly believe such an approach is essential for effectiveness (Bresnahan et al, 2002;Delery & Doty, 1996). Managers who view their employees as having the potential to grow have been shown to provide employees with a developmental environment (Heslin, Vandewalle, & Latham, 2006) and this might extend to managers designing better work. Parker & Andrei (2014) showed that individuals who had enriched work designs themselves were more likely to design enriched work designs for others, suggesting a positive spiral born out of experience.…”
Section: Future Directionsmentioning
confidence: 99%